Differences in Teacher Burnout Between Schools: Exploring the Effect of Proactive Strategies on Burnout Trajectories - Tikkanen, Lotta; Haverinen, Kaisa; Pyhältö, Kirsi; Pietarinen, Janne; Soini, Tiina (Frontiers in Education, 2022)
Differences in teacher burnout between schools are likely to occur due to differences in the quantity and quality of interaction within the schools. Multilevel latent growth curve analyses of burnout symptoms were performed on three-wave longitudinal data collected from 2,619 teachers in 75 schools in Finland. The results showed that differences in teacher burnout between schools were pronounced in cynicism, followed by emotional exhaustion. Organizational factors were not strong predictors of differences in teacher burnout. Proactive co-regulation strategies were related to lower levels of teachers’ cynicism about the professional community, implying that they might be useful in preventing the teachers’ cynicism at the school level.